Investigation of job satisfaction with training effectiveness through workload adjustment and work motivation - Abdul Wahid Alfarizi; Rustandi Rustandi; Eman Diantoro; Didit Haryadi; Syaechurodji Syaechurodji (International Journal of Applied Finance and Business Studies, 2026)
This study aims to analyze the effect of training on employee job satisfaction, focusing on workload and motivation. This research proposes that practical training can reduce workload, increase motivation, and ultimately increase employee job satisfaction. The research method used was quantitative, with an association approach, identifying the relationship between the variables. The research population consisted of 199 employees of the Cilegon City Public Works and Spatial Planning Office, with a total sampling technique. Data collection was conducted using a Likert-scale questionnaire. For data analysis, Structural Equation Modeling (SEM) was used with SmartPLS 4.0. The results of the study show that training has no direct effect on job satisfaction; however, it does have a significant effect on work motivation and workload, which, in turn, affect job satisfaction. Training that is relevant and tailored to employees' needs has been proven to reduce perceived workload, increase motivation, and boost job satisfaction. These findings make an important contribution to the development of human resource management strategies to improve employee performance and satisfaction in the public sector. It is hoped that this research can make a theoretical contribution to the literature in this context, of course, in the context of human resource management.